Can Religiosity Reduce Corruption Intention In Civil Servant? - Eka Aprilia; Indrayati Sri Maulina (IJIP : Indonesian Journal of Islamic Psychology, 2023)
Aceh Province is an area that has special autonomy and authority in regulating regional policies. One of them is regional financial management based on facts that are vulnerable to corruption. Corruption is a deviant behavior that is manifested from misuse of tasks for personal gain, other people and institutions. Corruption is an act that is prohibited by religion, but corruption behavior still occurs. Religiosity should be an individual defense to not commit corruption. The purpose of this study was to determine the relationship between religiosity and the intention of corruption among civil servants in Aceh provincial government agencies. This research uses quantitative research method with incidental sampling technique. The sample in this study were 350 respondents (n = 350) from eight Aceh provincial government agencies. The results of this study indicate that there is a negative relationship between religiosity and corrupt intentions of civil servants, with the meaning that the higher the religiosity, the lower the intention of corruption.